A proposed model of ICT facilities in the central zone vocational colleges, Malaysia - Thamarai Thamodharan; Muhammad Faizal A. Ghani (International Journal of Evaluation and Research in Education (IJERE), 2023)
The tide of globalization is moving so fast nowadays. Changes and its development are quite difficult to curb from spreading in our lives. These developments continue to have a positive impact on the community and no less giving various challenges to all of us especially to the world of education. The competency factor of the lecturer should increase in line with the changing environment. The opposite situation occurs in some educational institutions in Malaysia, such as vocational colleges (KV). Thus, the implementation of this study aimed to analyze the internal environment of vocational colleges involving information and communication technology (ICT) facilities as well as the effectiveness of ICT vocational colleges. Inferential analysis was used to identify contribution of exogenous variable to endogenous variable through Structural Equation Modeling (SEM-AMOS). To achieve the objectives of the study, a survey - type quantitative study design was implemented. Questionnaire instruments were distributed to 388 vocational college lecturers in the central zone of Malaysia using stratified random sampling. Furthermore, the questionnaire data were analyzed using Statistical Package for the Social Science (SPSS) version 25. The findings showed that there is a significant relationship between technological facilities (such as computers) with ICT effectiveness when p<0.05. In terms of moderators, the demographics of lecturers, namely gender, age and computer usage practices of KV lecturers affect the effectiveness of ICT KV when the mean score exceed 8.50. Furthermore, the developed model also meets the model fit indices requirements with RMSEA value at 0.060, CFI=0.973, TLI=0.968, Chisq/df=2.380 and GFI=0. 901.The implications of the study indicate that the role of lecturers as educators is important in developing appropriate reforms in supporting the innovations that take place in educational organizations.